Reading Trigunas in RK Narayan’s “Malgudi Days” - Chhetry, Tek Bahadur (Saptagandaki Journal, 2023)
This research paper explores the psychological concerns of the personalities in RK Narayan’s short stories from “Malgudi Days” where his characters of the upper class and patriarchy predominantly possess the Tamasic qualities while the needy as well as low caste people behold both Rajasic and Sattvic ones. The three stories- “Leela’s Friend,” “A Willing Slave”, and “Wife’s Holiday” are purposively chosen from Lawley Road collection to study character personalities in relation to the Trigunas’ abstract meaning explicated in the Bhagavad Gita (Chapters 14-18). The study critically analyzes the characters as to see how one Guna predominates over the other two and makes the personality act through one’s intellect, ego and mind. For this, my paper will largely rely on the textual content of the selected stories and their personalities in justifying the issue. Given the Gunas determine the quality of thoughts, emotions and actions in a person, there is a dire need of Sattvic qualities for everyone in the world that eventually opens the spot for self-realization. Nevertheless, the rampant are Rajasic and Tamasic Gunas in human. The study is going to be important because each individual is to be identified with their true qualities of thought to transform themselves into the Sattvic qualities so as to achieve an effortless excellence and lead a happy life with self-complacency.